Use of harsh physical discipline and developmental outcomes in adolescence - BENDER, HEATHER L. (2007)
A history of exposure to harsh physical discipline has been linked to negative outcomes for children, ranging from conduct disorder to depression and low self-esteem. The present study extends this work into adolescence, and examines the relationship of lifetime histories of harsh discipline to adolescents’ internalizing and externalizing symptoms and to their developing capacities for establishing autonomy and relatedness in family interactions. Adolescent and parent reports of harsh discipline, independently coded observations of conflictual interactions, and adolescent reports of symptoms were obtained for 141 adolescents at age 16. Both parents’ use of harsh discipline was related to greater adolescent depression and externalizing behavior, even when these effects were examined over and above the effects of other parenting measures known to account for these symptoms. Adolescents exposed to harsh discipline from mothers were also less likely to appear warm and engaged during an interaction task with their mothers. It is suggested that a history of harsh discipline is associated not only with social and emotional functioning, but also with the developmental task of autonomy and relatedness.